2003
DOI: 10.1037/1040-3590.15.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Screening for posttraumatic stress disorder: An evaluation of two self-report scales among crime victims.

Abstract: The validity of the Impact of Events Scale (IES) and the Posttraumatic Stress Disorder (PTSD) Symptom Scale, Self-Report version (PSS-SR) was examined among crime victims. Both instruments performed well as screeners for PTSD. For the IES, sensitivity ranged between .93 and 1.00; for the PSS-SR, sensitivity ranged between .80 and .90. Specificity for the IES ranged between .78 and .84 and for the PSS-SR ranged between .84 and .88. Some individual items from the 2 scales performed just as well as the total scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
143
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(151 citation statements)
references
References 37 publications
4
143
1
3
Order By: Relevance
“…For example, a Dutch study of pain and stress in burn victims found that IES scores > 26 were indicative of serious PTSD (Taal and Faber 1997). As a screening measure for PTSD, the sensitivity of the IES ranges from 0.94 to 1.00 and the specificity ranges from 0.78 to 0.84 (Wohlfarth et al 2003). More recently, it has been suggested that additional items on hyper-arousal could be added to the IES (Weiss and Marmar 1997).…”
Section: Posttraumatic Stress Disorder Symptomsmentioning
confidence: 99%
“…For example, a Dutch study of pain and stress in burn victims found that IES scores > 26 were indicative of serious PTSD (Taal and Faber 1997). As a screening measure for PTSD, the sensitivity of the IES ranges from 0.94 to 1.00 and the specificity ranges from 0.78 to 0.84 (Wohlfarth et al 2003). More recently, it has been suggested that additional items on hyper-arousal could be added to the IES (Weiss and Marmar 1997).…”
Section: Posttraumatic Stress Disorder Symptomsmentioning
confidence: 99%
“…A 4-point Likert scale will be used ranging from 0 (not at all) to 5 (often). The cut-off score for a probable diagnosis of PTSD is ≄ 33 39,40 . The Dutch translation of the IES-R has been found to be valid and reliable 41 .…”
Section: Acute Stress Disorder and Post Traumatic Stress Disordermentioning
confidence: 99%
“…For example, a Dutch study of pain and stress in burn victims found that IES scores >26 were indicative of serious PTSD (Taal and Faber, 1997). As a screening measure for PTSD, the sensitivity of the IES ranges from 0.94 to 1.00 and the specificity ranges from 0.78 to 0.84 (Wohlfarth et al, 2003). More recently, it has been suggested that additional items on hyper-arousal could be added to the IES (Weiss and Marmar, 1997).…”
Section: Posttraumatic Stress Disorder Symptomsmentioning
confidence: 99%